ANALYSIS OF THE DESIGN, IMPLEMENTATION, AND EVALUATION OF 21ST CENTURY SKILLS EDUCATION IN CLASS X AT STATE SENIOR HIGH SCHOOL - Abdillah, Bayu Surya; Medriati, Rosane; Putri, Desy Hanisa (Jurnal Pendidikan Matematika dan IPA, 2024)
This research was conducted with the aim of describing 1). Analyzing the design of learning implementation, 2). Analyzing the learning process (RPP), 3). Analyzing the evaluation of 21st century learning in class X of SMAN 7 Bengkulu City. The research method used is a descriptive method, using qualitative descriptive analysis techniques. The samples used were students and physics teachers of class This research shows that the results of the analysis of learning implementation plans (RPP) are based on 21st century learning skills with a percentage of 86.87%, consisting of aspects, namely planning with a percentage of 87.50%, implementation with a percentage of 85.62%. and evaluation of 21st century learning with a percentage of 87.50%. So from the results of this analysis it can be concluded that the design for implementing 21st century skills learning is in the good category.